Colette's republic : work, gender, and popular culture in France, 1870-1914 - Tilburg, Patricia A. (ACLS Humanities E-Book., 2009)
"In France's Third Republic, secularism was, for its adherents, a new faith, a civic religion founded on a rabid belief in progress and the Enlightenment conviction that men (and women) could remake their world. And yet with all of its pragmatic smoothing over of the supernatural edges of Catholicism, the Third Republic engendered its own fantastical ways of seeing by embracing observation, corporeal dynamism, and imaginative introspection. How these republican ideals and the new national education system of the 1870s and 80s--the structure meant to impart these ideals--shaped belle époque popular culture is the focus of this book. The author reassesses the meaning of secularization and offers a cultural history of this period by way of an interrogation of several fraught episodes which, although seemingly disconnected, shared an attachment to the potent moral and aesthetic directives of French republicanism: a village's battle to secularize its schools, a scandalous novel, a vaudeville hit featuring a nude celebrity, and a craze for female boxing. Beginning with the writer and performer Colette (1873-1954) as a point of entry, this re-evaluation of belle époque popular culture probes the startling connections between republican values of labor and physical health on the one hand, and the cultural innovations of the decades preceding World War I on the other."--